Multifunctional magnet-polymer transducers - Ahmed, Anansa Sasha Shakil (2016)
A key goal of current research is to develop the next generation of materials, structures and systems which can mimic “life” functions, thus imparting extended service lifetime and reliability, while also decreasing maintenance and operating costs. Living organisms can sense and react to environmental stimuli, e.g., they can sense damage to their structure and respond appropriately via a healing mechanism. This phenomenon can occur over multiple cycles during its lifetime. The objective of this thesis is to develop a bioinspired artificial material which can mimic the functions of multicycle damage sensing, self healing and actuation. This material will be of great significance in applications such as biomedical coatings or novel aircraft wing “skin” where damage sensing, healing, flexibility, actuation capability and extended lifetimes are required. Magnet filler-polymer matrix composites (Magpol) are an attractive material to combine multiple functions. This is because the inherent properties of both magnetic fillers and the polymer matrix can be readily tuned. Magpol can exhibit quick response, remote contactless actuation, high actuation strain and strain rate, remote heating in alternating magnetic fields (AMF), and self-sensing. These capabilities enable Magpol to respond to a range of stimuli to trigger self healing, sensing and actuation. In this work, a Magnet-polymer composite capable of actuation, damage sensing and self healing was developed by tuning the properties of a magnetic ferrite nanoparticle filler, commercial biocompatible thermoplastic shape memory matrix and stilbene dye molecules. The Curie temperature (Tc) of the Mn-Zn ferrite nanoparticles was tuned to provide a “failsafe” temperature stimulus required for sensing and healing via the application of an AMF; a constant (DC) magnetic field was utilized to induce actuation. Bis(benzoxazolyl)stilbene (BBS) mechanochromic dye was utilized as a colour changing damage sensor, while the shape memory properties of poly (ethylene-co-vinyl acetate) (EVA) was used to extend these functions over multiple cycles, increasing Magpol’s service life. Each of the three functionalities was studied and Magpol’s performance was compared to competing technologies through Ashby charts. The self healing ability of Magpol was evaluated over multiple cycles of damage and repair by subjecting it to multiple types of damage, such as tear tests, wear etc. The first study of the Tc dependence on healing efficiency was conducted and the healing efficiency obtained was comparable to self healing ionomers and supramolecular polymers. The heating behaviour of the magnetic nanoparticles and the healing efficiency was modelled and good agreement was found with experimental results. In a manner similar to biological sensing, colour change was used as a damage sensing mechanism. By studying the BBS interactions in the strained matrix, a linear relationship between the visible colour change and strain/damage was demonstrated in Magpol. The shape recovery property of Magpol was also utilized to develop the first multicycle thermoplastic strain sensor. These self healing and sensing properties are a prerequisite of candidate biomimetic materials for flexible coatings or morphing structures. The actuation behaviour in bending and buckling modes was also studied to demonstrate the work capability of Magpol. The stress, strain and work output was determined for each mode. The buckling mode of actuation showed the highest work output of 16 J/kg, which is comparable with other electroactive polymers. The Mn-Zn ferrite nanoparticle filler loading was optimized for each case and the actuation behaviour of Magpol was also compared to an analytical model. In both cases the experiments matched well with modelling results. To demonstrate the significance of multifunctional Magpol in a technological application, a novel proof-of-concept biomedical guidewire coating was developed. The coating was capable of sensing wear, undergoing self healing and targeted positioning in a magnetic field. Thus, Magpol possesses attractive characteristics for the development of multifunctional, bioinspired materials with practical applications.